2009
DOI: 10.1016/j.marpol.2008.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Public awareness of marine environmental issues in the UK

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. This paper presents the results of a survey of public awareness of marine environmental issues within the contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 8 publications
4
55
0
1
Order By: Relevance
“…While some certification programs have played a role in improving fisheries sustainability and possibly aided interested consumers [49], a greater emphasis should be placed on activating the public's role not just as consumers, but also as citizens too [32]. While efforts have been made to conduct public outreach campaigns, further investigation is still needed as to how to better engage the public as consumers and as citizens to improve the stewardship of wild capture fisheries [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…While some certification programs have played a role in improving fisheries sustainability and possibly aided interested consumers [49], a greater emphasis should be placed on activating the public's role not just as consumers, but also as citizens too [32]. While efforts have been made to conduct public outreach campaigns, further investigation is still needed as to how to better engage the public as consumers and as citizens to improve the stewardship of wild capture fisheries [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…The limited body of research on the public understanding of the ocean suggests that the public is not well versed in ocean-related functions, processes, and issues [69,58,66,27,38]. A national study found that only 24% of Americans had heard of OA, and only 32% of this subpopulation recognizes CO 2 as a driver [38].…”
Section: Public Understanding Of Oceans and Ocean Acidificationmentioning
confidence: 99%
“…To ensure sustainable use of ocean resources there is a need for both top-down and bottom-up approaches; that is, responsible policies, regulations and management strategies [29] as well as individual behavior changes [27]. However, it has become increasingly evident that citizens in many countries have a poor understanding of marine science and ocean issues [36,4,37,35,21,17], which may act as a barrier to individual behavior changes [20]. Furthermore, there is growing awareness that formal education curricula do not adequately communicate ocean science to young people, as low levels of ocean science understanding are evident among students in a number of countries [6,7,15,3,14,35].…”
Section: Introductionmentioning
confidence: 99%